Republic of Belarus : 2009 Article IV Consultation and Second Review Under the Stand-By Arrangement-Staff Report Informational Annex; Staff Statement; Public Information Notice on the Executive Board Discussion; and Press Release. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that Belarus has so far escaped a significant fall in output, despite a sharp fall in external demand. GDP declined 0.5 percent year over year in the first eight months of 2009, comparing favorably to Belarus' main trading partners. Economic activity has been bolstered by strong domestic demand, especially for housing construction financed under government programs. Executive Directors have applauded the authorities' commitment to a tight fiscal policy, with revenue shortfalls being offset by spending restraint while protecting priority social spending.